Effects of radiofrequency fields on RAS and ERK kinases activity in live cells using the bioluminescence resonance energy transfer technique. (2nd June 2020) - Poque, Emmanuelle; Arnaud-Cormos, Delia; Patrignoni, Lorenza; Ruigrok, Hermanus J.; Poulletier De Gannes, Florence; Hurtier, Annabelle; Renom, Rémy; Garenne, André; Lagroye, Isabelle; Lévêque, Philippe; Percherancier, Yann
Abstract: Purpose: The present study was conducted to re-evaluate the effect of low-level 1800 MHz RF signals on RAS/MAPK activation in live cells. Material and methods: Using Bioluminescence Resonance Energy Transfer technique (BRET), we assessed the effect of Continuous wave (CW) and Global System for Mobile (GSM)-modulated 1800 MHz signals (up to 2 W/kg) on ERK and RAS kinases' activity in live HuH7 cells. Results: We found that radiofrequency field (RF) exposure for 24 h altered neither basal level of RAS and ERK activation nor the potency of phorbol-12-myristate-13-acetate (PMA) to activate RAS and ERK kinases. However, we found that exposure to GSM-modulated 1800 MHz signals at 2 W/kg decreased the PMA maximal efficacy to activate both RAS and ERK kinases' activity. Exposure with CW 1800 MHz signal at 2 W/kg only decreased maximal efficacy of PMA to activate ERK but not RAS. No effects of RF exposure at 0.5 W/kg was observed on maximal efficacy of PMA to activate either RAS or ERK whatever the signal used. Conclusions: Our results indicate that RF exposure decreases the efficiency of the cascade of events, which, from the binding of PMA to its receptor(s), leads to the activation of RAS and ERK kinases.